2018
DOI: 10.1002/ldr.2914
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cadmium, copper, lead, and zinc in mudflat salt‐soils amended with sewage sludge

Abstract: Applying sewage sludge to mudflat salt‐soils can rapidly improve soil physicochemical properties and enhance pollution potential. Nevertheless, the heavy metal distribution in leachate and mudflat salt‐soils with sludge amendment remains unclear. The present work was aimed primarily at investigating the fates of Cd, Cu, Pb, and Zn in mudflat salt‐soils amended by sludge. A leaching column experiment in a greenhouse was conducted to analyze the leaching losses of the metals in the sludge‐amended soils and to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Some studies also reported that DOC plays a significant role in mediating metal's solubility and mobility due to its stronger complexation ability (Weng et al, 2002;Gao et al, 2018). The release of low-molecular-weight organic matter (a major constituent of DOC) from biodegradation of wheat straw increased DOC content in soil leachate, which combined Cd and reduced the previously adsorption of Cd on soil surfaces, thus enhancing Cd solubility (Antoniadis and Alloway, 2002;Bai et al, 2018). This conclusion was further supported by the data obtained in which the proportion of available Cd decreased in the remaining soil treated with wheat straw in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also reported that DOC plays a significant role in mediating metal's solubility and mobility due to its stronger complexation ability (Weng et al, 2002;Gao et al, 2018). The release of low-molecular-weight organic matter (a major constituent of DOC) from biodegradation of wheat straw increased DOC content in soil leachate, which combined Cd and reduced the previously adsorption of Cd on soil surfaces, thus enhancing Cd solubility (Antoniadis and Alloway, 2002;Bai et al, 2018). This conclusion was further supported by the data obtained in which the proportion of available Cd decreased in the remaining soil treated with wheat straw in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Municipal sewage sludge abundant in organic matter and other nutrients available to plants has the potential use in mudflat as amendment and original fertilizers. Bai, Xue, et al () and Bai, Yan, et al () discussed the current status of mudflat‐soil amendment using sewage sludge basing on the study of different parts in Jiangsu Province, China, for many years, confirming that sewage sludge application could elevate soil organic matter content and improve soil physicochemical properties subsequently due to raising soil porosity, available nitrogen and phosphorus, and the decrease in bulk density, salinity, and pH in the salt‐soil. It is a general fact that the viability to use sewage sludge as organic amendment is conditioning with its content of heavy metals or other contaminants, and both of them strongly link with the origin of sewage sludge: industrial or residential cities.…”
Section: Representative Advancesmentioning
confidence: 99%
“…Different types of organic amendments such as green manures, farmyard and poultry manures, compost, food‐processing wastes, and biochar have been applied to soils for enhancing soil quality (Bhaduri et al, ; Liu et al, ; Xu, Zhang, Shao, & Sun, ; Yang, Bian, Tang, Zhou, & Li, ). Among these, green manure is a promising way with long‐term effects and low cost (Bai et al, ; Bai, Xu, et al, ; Bai, Yan, et al, ; Bai, Zou, et al, ; Li et al, ; Maltas, Kebli, Oberholzer, Weisskopf, & Sinaj, ; Meier et al, ; Xu et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%